Pelaksanaan model pembelajaran TGT (Teams Games Tournaments) menggunakan quizizz pada peserta didik kelas X D mata pelajaran sosiologi di SMA Muhammadiyah 1 Pontianak - Hariani, Wiwin; Ramadhan, Iwan; Imanulyaqin, Muhammad Nur (Universitas Tanjungpura, 2025)
This study aims to analyze the implementation of the Team Games Tournament (TGT) learning model combined with the Quizizz application for Grade X D students in the Sociology subject at SMA Muhammadiyah 1 Pontianak. The research employed a qualitative approach with a descriptive design. Data were collected through observations, interviews, and evaluation tests to obtain a comprehensive overview of the learning process and outcomes. The results indicate that the application of the TGT model supported by Quizizz increased students